The Role of Intergenerational Leadership in Enhancing Engagement and Communication of Generation Z in The Workplace - Nguyen Phu, Huy; Martínez Pantoja, Yadira Ixchel; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the impact of intergenerational leadership on Generation Z’s engagement and communication in the workplace. As Generation Z becomes a significant part of the workforce, understanding how they interact with supervisors from older generations such as Millennials, Generation X, and Baby Boomers, is increasingly important. The study aims to identify key factors influencing engagement and communication, highlighting generational differences in the workplace. By conducting a mixed-method, the findings reveal that Generation Z values open communication, consistent leadership, and generational adaptation in the workplace. Challenges such as emotional disconnect, inconsistent guidelines, and differing work-life balance expectations emerged as recurring themes. The findings offer practical insights for organizations seeking to enhance cross-generational collaboration and foster inclusive, supportive work environments.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses